2018
DOI: 10.3390/molecules23123345
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cucurbitacin B Derivatives as Potential Anti-Hepatocellular Carcinoma Agents

Abstract: Cucurbitacin B shows potent activity against tumor cells, but its high toxicity limits its application in the clinic. A series of cucurbitacin B derivatives was synthesized and evaluated for their anti-hepatocellular carcinoma (HCC) activities against the HepG-2 cell line. These compounds were also tested for their toxicity against the L-O2 normal cell line. The compound with the most potential, 10b, exhibited potent activity against the HepG-2 cell line with an IC50 value of 0.63 μM. Moreover, compound 10b sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…For instance, cucurbitacins B, D, E, and I are the most wildly studied variants and exhibit general in vitro and in vivo anti-cancer effects. Cucurbitacin B shows significant inhibition effects in breast cancer (Jin et al, 2018), liver cancer (Ge et al, 2018), and glioblastoma multiforme (Qin et al, 2018); cucurbitacin E exerts anti-cancer activities in treating brain cancer (Cheng et al, 2019) and gastric cancer (Jafargholizadeh et al, 2018); cucurbitacin D is effective to treat cervical cancer (Sikander et al, 2016) and breast cancer (Ku et al, 2015); and cucurbitacin I also processes anti-cancer activities (Kim and Kim, 2015; Wu et al, 2016; Ni et al, 2018). Moreover, cucurbitacins can also inhibit tumor angiogenesis (Touihri-Barakati et al, 2017; Piao et al, 2018), enhance anti-proliferative activity of chemotherapy drugs (Sadzuka et al, 2010; Aribi et al, 2013), and suppress cancer cell stemness (Shukla et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, cucurbitacins B, D, E, and I are the most wildly studied variants and exhibit general in vitro and in vivo anti-cancer effects. Cucurbitacin B shows significant inhibition effects in breast cancer (Jin et al, 2018), liver cancer (Ge et al, 2018), and glioblastoma multiforme (Qin et al, 2018); cucurbitacin E exerts anti-cancer activities in treating brain cancer (Cheng et al, 2019) and gastric cancer (Jafargholizadeh et al, 2018); cucurbitacin D is effective to treat cervical cancer (Sikander et al, 2016) and breast cancer (Ku et al, 2015); and cucurbitacin I also processes anti-cancer activities (Kim and Kim, 2015; Wu et al, 2016; Ni et al, 2018). Moreover, cucurbitacins can also inhibit tumor angiogenesis (Touihri-Barakati et al, 2017; Piao et al, 2018), enhance anti-proliferative activity of chemotherapy drugs (Sadzuka et al, 2010; Aribi et al, 2013), and suppress cancer cell stemness (Shukla et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies have been focused on tackling this side effect, and some cucurbitacin B derivatives have been synthesized to screen for effective cancer therapy with safety and tolerability. Compound 10b, one of the derivatives of cucurbitacin B, shows more potent anti-cancer activity than cucurbitacin B [496]. The in vivo acute toxicity study also shows that compound 10b has better tolerability and safety than cucurbitacin B.…”
Section: Cucurbitacinsmentioning
confidence: 93%
“…Moreover, diverse STAT3 inhibitors have already been shown to be effective by inducing the apoptosis of tumor cells [ 10 , 11 , 12 , 13 , 14 ]. Cucurbitacins are highly oxygenated tetracyclic triterpenes, which show potent pharmacological effects, including anticancer activity [ 15 , 16 , 17 , 18 , 19 , 20 ]. Moreover, the dose necessary for cucurbitacins to present a therapeutical effect is much lower than the toxic dose, thus increasing their potential as therapeutic agents [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the dose necessary for cucurbitacins to present a therapeutical effect is much lower than the toxic dose, thus increasing their potential as therapeutic agents [ 19 ]. Among cucurbitacin derivatives, cucurbitacin-D (CuD) showed an effective inhibitory effect on the proliferation of colon, breast, lung, cervical, and prostate cancer cell lines as a result of Janus kinase/signal transducer activator of transcription 3 (JAK/STAT3) signaling pathway inhibition [ 15 , 16 , 18 , 19 , 20 ]. Studies also identified that the combination of cucurbitacins and anticancer agents can promote a synergism and may augment the chemotherapeutic effects via suppression of STAT3, being promising for tumor treatment [ 17 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation